ANALISIS KELAYAKAN USAHA INDUSTRI RUMAH TANGGA KERIPIK SINGKONG MENTAH DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Rahmawati Nunik; Pailis Armas Eka; Isyandi B H (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the feasibility of the home industry of raw cassava chips in Tenayan Raya District, Pekanbaru City. The population and sample in this study was the home industry of raw cassava chips in Tenayan Raya Subdistrict, amounting to 10 businesses. The data used in this study are primary and secondary data. Data collection techniques through interview methods and recording methods. The data analysis method uses descriptive analysis covering market aspects and technical and technological aspects, socioeconomic aspects, aspects of human resources, while quantitative analysis is performed to analyze financial aspects such as Net Present Value (NPV), Benefit Cost Ratio (B / C Ratio) , Net Benefit Cost Ratio (Net B / C Ratio), and Break Event Point (BEP) The results of this study indicate that the home industry of raw cassava chips in the Tenayan Raya District, Pekanbaru City is worth working on. This can be seen from the results of financial analysis which shows the average NPV value of Rp. 41,612,964,991> 0, the average B / C Ratio is 1.49> 1, the average Net B / C Ratio is 4.25, and the production BEP analysis reaches 748.47kg, 760.10kg, respectively 547.59kg, 691.71kg, 321.85kg, 566.38kg, 513.17kg, 443.01kg, 358.91kg, and 456, 06kg with the selling price per kilogram of Rp.12,000 respectivelyKeywords: Cassava Chips, Home Industry, and Feasibility